(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Serious human health impacts have been observed worldwide due to several life threatening diseases such as cancer, candidiasis, hepatic coma, and gastritis etc. Exploration of nature for the treatment of such fatal diseases is an area of immense interest for the scientific community. Based on this idea, the genus Aspergillus was selected to discover its hidden therapeutic potential. The genus Aspergillus is known to possess several biologically active compounds. The current research aimed to assess the biological and pharmacological potency of the extracts of less studied Aspergillus ficuum (FCBP-DNA-1266) (A. ficuum) employing experimental and bioinformatics approaches. The disc diffusion method was used for the antifungal investigation, and the MTT assay was performed to assess the anticancer effects. Mice were employed as an in vivo model to evaluate the antispasmodic effects. A standard spectrophotometric technique was applied to gauge the urease inhibitory activity. The antifungal studies indicate that both n-hexane and ethyl acetate extracts were significantly active against Candida albicans (C. albicans) with their zone of inhibitions (ZOI) values reported as 19 ± 1.06 mm and 25 ± 0.55 mm, respectively at a dose of 30 μg.mL−1. In vitro cytotoxicity assay against HeLa, fibroblast 3T3, prostate PC3, and breast MCF-7 cancer cell lines was performed. The ethyl acetate extract of A. ficuum was found to be significantly active against MCF-7 with its IC50 value of 43.88 μg.mL−1.